A New Phallic Carving from Roman Catterick. (2nd May 2016) - Parker, Adam; Ross, Cath
ABSTRACT: A phallic carving excavated by Northern Archaeological Associates in 2014 during investigations at Catterick, North Yorkshire, contained unique artistic features for a carving of this type in Roman Britain. Excavations were carried out as part of the A1 Leeming to Barton road upgrade scheme. The two features — a projecting line of ejaculate and an incised, triangular object — are here considered within the wider evidence base for phallic imagery in Roman Britain.